Guided self-help for functional (psychogenic) symptoms: a randomized controlled efficacy trial. - Sharpe, M; Walker, J; Williams, C; Stone, J; Cavanagh, J; Murray, G; Butcher, I; Duncan, R; Smith, S; Carson, A (2011)
OBJECTIVES: Functional (psychogenic or somatoform) symptoms are common in neurology clinics. Cognitive-behavioral therapy (CBT) can be an effective treatment, but there are major obstacles to its provision in practice. We tested the hypothesis that adding CBT-based guided self-help (GSH) to the usual care (UC) received by patients improves outcomes. METHODS: We conducted a randomized trial in 2 neurology services in the United Kingdom. Outpatients with functional symptoms (rated by the neurologist as "not at all" or only "somewhat" explained by organic disease) were randomly allocated to UC or UC plus GSH. GSH comprised a self-help manual and 4 half-hour guidance sessions. The primary outcome was self-rated health on a 5-point clinical global improvement scale (CGI) at 3 months. Secondary outcomes were measured at 3 and 6 months. RESULTS: In this trial, 127 participants were enrolled, and primary outcome data were collected for 125. Participants allocated to GSH reported greater improvement on the primary outcome (adjusted common odds ratio on the CGI 2.36 [95% confidence interval 1.17-4.74; p = 0.016]). The absolute difference in proportion "better" or "much better" was 13% (number needed to treat was 8). At 6 months the treatment effect was no longer statistically significant on the CGI but was apparent in symptom improvement and in physical functioning. CONCLUSIONS: CBT-based GSH is feasible to implement and efficacious. Further evaluation is indicated. CLASSIFICATION OF EVIDENCE: This study provides Class III evidence that CBT-based GSH therapy improves self-reported general health, as measured by the CGI, in patients with functional neurologic symptoms.